Prospective properties of Gigantochloa Scortechinii (buluh semantan) fibre for biocomposite material / Anith Athierah Aziz - Aziz, Anith Athierah (2022)
Bio-composites are essential materials created from renewable resources that biodegrade and sustainable such as bamboo fibre to produce a new generation of composites for construction industry used. Even though most bamboo grows in forest, there is still a scarcity of data on the morphology, physical, chemical, and mechanical properties of cultivated wild bamboo in Malaysian forest. Hence, the aim of this research is to determine the physical, chemical, and mechanical properties of species Gigantochloa Scortechinii (Buluh Semantan) suitable criteria for bio-composite material. The research objective is to analyse the physical and chemical properties of bamboo culm that influenced the mechanical strength of bamboo fibre and the suitability of fibre as bio-composite material. It is revealed that the suitable characteristics of bamboo fibre as bio-composite material are lower in moisture content, higher density, has better mechanical strength such as tensile strength and modulus of elasticity. Thus, this research presents on Sample A and Sample B of Buluh Semantan species that was discover in Royal Belum State Park. Several experimentations were conducted on bamboo fibre and bamboo culm by referring to ISO 22157 and TAPPI standard procedure.